Diability and poverty : the need for a more nuanced understanding of implications for development policy and practice - Groce, Nora (2011)
Reviews existing knowledge and theory regarding the disability-poverty nexus. Using both established theoretical constructs and field-based data, it attempts to identify what knowledge gaps exist and need to be addressed with future research.